Describing and characterising on‐demand delivery of unhealthy commodities in New Zealand - Hannah Miles; Brylie Apeldoorn; Christina McKerchar; Angela Curl; Rose Crossin (Elsevier, 2022)
Abstract Objective: To determine the geographical location and characteristics of on‐demand delivery services operating in New Zealand. Methods: We systematically searched the web and application (app) stores for on‐demand services offering rapid delivery of food, alcohol, cigarettes or vaping products in New Zealand and mapped their geographic location as of May 2021. Using desktop review, data on service characteristics were collected and stratified including: types of commodities available, promotion strategies, and the legal aspects of access to age‐restricted items. Results: On‐demand services for food, alcohol and nicotine products operate across urban and rural New Zealand. All services offered personal memberships and 97% used promotions. All services offering restricted items had an age verification process, however, only 87% had birth date entry and 73% had an 18+ message pop‐up on website entry. Only 60% of services appeared to have number limits on restricted items. Conclusions: Much of New Zealand is serviced by on‐demand delivery services. Implications for public health: The trend towards on‐demand delivery services may increase unhealthy food, alcohol and nicotine‐related harms and it undermines current government actions, e.g. the Smokefree 2025 goal. This research informs policy to reduce the future health burden.